ASSESSMENT OF FISHING UNITS BASED ON BIOLOGICAL, TECHNICAL, AND FINANCIAL ASPECTS AT SUNGAILIAT NUSANTARA FISHERIES PORT: PENILAIAN UNIT PENANGKAPAN IKAN BERDASARKAN ASPEK BIOLOGI, TEKNIS, DAN FINANSIAL DI PELABUHAN PERIKANAN NUSANTARA SUNGAILIAT - Tardha Amirah Adibah; Mohammad Imron; Mulyono Mulyono (Jurnal Teknologi Perikanan dan Kelautan, 2026)
Sungailiat Nusantara Fisheries Port (PPN Sungailiat) is one of the fishing ports that manages fishing activities in Bangka Waters. Bangka waters have relatively high fisheries production, but the utilization of their fishery potential was not optimal, reaching only around 21.6% of the sustainable potential. This situation is suspected to be caused by the use of traditional fishing gear and inadequate fishing boats. Therefore, it is necessary to develop fishing units to optimize the utilization of the fisheries' potential. This study aims to determine priority fishing units based on biological, technical, and financial aspects. The research employed a survey of 85 fishers' respondents. Data were analyzed using a standardized scoring analysis based on the multi-criterion analysis (MCA) model. The results show that handlines and fish traps lead in biological and technical aspects attributed to their superior catch composition and operational feasibility. Furthermore, fish traps exhibit the highest financial viability with higher returns per fisher. Overall, the results of the combined analysis indicate that fish traps are the primary fishing unit to be developed in PPN Sungailiat, with a V(A) value of 2.87.